‘The Problem of Prostitution’: Repressive policies in the name of migration control, public order, and women’s rights in France - Calderaro, Charlène; Giametta, Calogero (Anti-Trafficking Review, 2019)
This article focuses on the political debates that led to the adoption of the sex purchase ban (commonly referred to as the Swedish or Nordic model) in France in April 2016. It examines the convergence of French mainstream feminists and traditional neo-abolitionist actors in the fight against prostitution, and its impact on sex workers’ rights and wellbeing. We argue that there is continuity between the effects produced by the ban on soliciting enacted in 2003 and those created by the law penalising clients passed in 2016. In discussing the current repression of sex work in France, we highlight how the construction of the ‘problem of prostitution’ should be seen in light of broader political anxieties over sexism in poor neighbourhoods and immigration control, which justify the national priorities of security and public order.